2018
DOI: 10.18805/ijar.b-923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yeast based mannan oligosaccharide (Actigen™) supplementation on growth, carcass characteristics and physiological response in broiler chickens

Abstract: The effect of a prebiotic mannan oligosaccharides (Actigen™) supplementation for 35 days was analyzed on growth, carcass traits and blood physiology of broilers. A total of 360-day-old broilers distributed under completely randomized design into four treatment groups with 24 replicates of 15 birds each was fed with Actigen™ supplemented diets @ 0.2, 0.4 and 0.6 g/Kg and a control diet. Data for growth performance were collected weekly while slaughtering data at 35th day. Results showed that the birds fed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
3
4
0
Order By: Relevance
“…They also reported that broiler thigh and breast weight were elevated after adding single or combined dietary supplements of MOS and probiotics. Yeast based MOS supplementation improved carcass characteristics and blood biochemical parameters in broiler chickens (26). Similar results were seen in our present study.…”
Section: Discussionsupporting
confidence: 92%
“…They also reported that broiler thigh and breast weight were elevated after adding single or combined dietary supplements of MOS and probiotics. Yeast based MOS supplementation improved carcass characteristics and blood biochemical parameters in broiler chickens (26). Similar results were seen in our present study.…”
Section: Discussionsupporting
confidence: 92%
“…Results ofMuhammad et al (2020) were also similar to our study they recorded that MOS supplemented group has signi cantly higher antibody titer against NDV as than control group but lower than probiotic group. Similar results were also found byWaqas et al (2019) as MOS supplemented group showed higher antibody titer against NDV as compared to control group.…”
supporting
confidence: 86%
“…Other studies demonstrated that prebiotic supplementation in the broiler diet had no significant difference in growth performance (Li et al, 2017;Zhou et al, 2019). As well, Waqas et al (2018) affirmed that the dietary prebiotic supplementation did not exert (P>0.05) body weight and body gain. Nevertheless, other researchers reported that supplementation of prebiotics had significantly improved productive traits (Munyaka et al, 2012;Bednarczyk et al, 2016;Adhikari and Kim 2017).…”
Section: Effect Of Prebiotic Supplementation On Productive Traitsmentioning
confidence: 69%